Differential role of angiogenesis and tumour cell proliferation in brain metastases according to primary tumour type: analysis of 639 cases. (February 2015) - Berghoff, Anna S.; Ilhan‐Mutlu, Aysegül; Dinhof, Carina; Magerle, Manuel; Hackl, Monika; Widhalm, Georg; Hainfellner, Johannes A.; Dieckmann, Karin; Pichler, Josef; Hutterer, Markus; Melchardt, Thomas; Bartsch, Rupert; et al.
Abstract : Aim: We aimed to characterize angiogenesis and proliferation and their correlation with clinical characteristics in a large brain metastasis (BM) series. Methods: Ki67 proliferation index, microvascular density (MVD) and hypoxia‐inducible factor 1 alpha (HIF‐1 alpha) index were determined by immunohistochemistry in BM and primary tumour specimens. Results: Six hundred thirty‐nine BM specimens of 639 patients with lung cancer (344/639; 53.8%), breast cancer (105/639; 16.4%), melanoma (67/639; 10.5%), renal cell carcinoma (RCC; 52/639; 8.1%) or colorectal cancer (CRC; 71/639; 11.1%) were available. Specimens of the corresponding primary tumour were available in 113/639 (17.7%) cases. Median Ki67 index was highest in CRC BM and lowest in RCC BM ( P < 0.001). MVD and HIF‐1 alpha index were both highest in RCC BM and lowest in melanoma BM ( P < 0.001). Significantly higher Ki67 indices, MVD and HIF‐1 alpha indices in the BM than in matched primary tumours were observed for breast cancer, non‐small cell lung cancer (NSCLC) and CRC. Correlation of tissue‐based parameters with overall survival in individual tumour types showed a favourable and independent prognostic impact of low Ki67 index [hazard ratio (HR) 1.015; P < 0.001] in NSCLC BM and of low Ki67 index (HR 1.027; P = 0.008) and high angiogenic activity (HR 1.877; P = 0.002) in RCC. Conclusion: Our data argue for differential pathobiological and clinical relevance of Ki67 index, HIF1‐alpha index and MVD between primary tumour types in BM patients. An independent prognostic impact of tissue‐based characteristics was observed in patients with BM from NSCLC and RCC, supporting the incorporation of these tissue‐based parameters into diagnosis‐specific prognostic scores.